Adsorption of nonionic surfactant on silica nanoparticles: structure and resultant interparticle interactions - Sharma, Kamendra P.; Aswal, Vinod K.; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2010)
Addition of nonionic surfactant, C(12)E(9), to an aqueous dispersion of charge stabilized silica nanoparticles renders particle aggregation reversible. In contrast, aggregation of the same silica particles in aqueous solutions is irreversible. We use a combination of small-angle X-ray scattering (SAXS) and contrast matching small-angle neutron scattering (SANS) to investigate interparticle interactions and microstructure in dispersions of silica particles in aqueous nonionic surfactant solutions. We show that the silica particles interact through a screened Coulombic interaction in aqueous dispersions; interestingly, this interparticle interaction is hard-sphere-like in surfactant solutions. In surfactant solutions, we show that the final surfactant-particle structure can be modeled as 14 micelles adsorbed (on average) on the surface of each silica particle. This gives rise to the short-range interparticle repulsion that makes particle aggregation reversible, and results in the hard sphere interparticle interaction potential. Finally, we show that adsorption of polyethylene imine on the surface of the silica particles prevents adsorption of surfactant micelles on the particle surface.